2021
DOI: 10.1002/jpen.2194
|View full text |Cite
|
Sign up to set email alerts
|

Initial development and validation of a novel nutrition risk, sarcopenia, and frailty assessment tool in mechanically ventilated critically ill patients: The NUTRIC‐SF score

Abstract: Background: Nutrition risk, sarcopenia, and frailty are interrelated. They may be due to suboptimal or prevented by optimal nutrition intake. The combination of nutrition risk (modified nutrition risk in the critically ill [mNUTRIC]), sarcopenia (SARC-F combined with calf circumference [SARC-CALF]), and frailty (clinical frailty scale [CFS]) in a single score may better predict adverse outcomes and prioritize resources for optimal nutrition in the intensive care unit (ICU) Methods: This is a retrospective anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…In addition, our results also showed an important aspect that the area of LM on the abdomen and muscle mass around the lumbar vertebrae was significantly reduced in CD patients compared to normal contrast after adjusting for the BMI. Depletion of lean body mass is associated with lower quality of life, and higher morbidity and mortality commonly occur as part of the aging process (2,23). At the same time, loss of muscle mass accelerated the BMD reduction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, our results also showed an important aspect that the area of LM on the abdomen and muscle mass around the lumbar vertebrae was significantly reduced in CD patients compared to normal contrast after adjusting for the BMI. Depletion of lean body mass is associated with lower quality of life, and higher morbidity and mortality commonly occur as part of the aging process (2,23). At the same time, loss of muscle mass accelerated the BMD reduction.…”
Section: Discussionmentioning
confidence: 99%
“…LM exerts an additional influence on the skeleton through regional muscle pull and contributes to the loading of the bone. Other possible mechanism is that these disorders are also a characteristic of malnutrition and chronic intestinal inflammation in CD (2). Moreover, it has been shown that increased muscle mass contributed to the increase in BMD and can reduce the vertebral fracture risk (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the proposed mNUTRIC-S2 score of this study, the NUTRIC-SF score (which combines the modified NUTRIC score with a measure of sarcopenia and frailty) [ 27 ], the NUTRIC-S score (which uses SAPS III instead of APACHE II) [ 28 ], the NUTRIC score, and CRP [ 29 ] are other versions of critical nutritional risk assessment tools, in addition to the NUTRIC and mNUTRIC scores. First, the NUTRIC-SF score is better than the mNUTRIC score, the SARC-CALF (a measure of sarcopenia risk combined with calf circumference), and the Clinical Frailty Scale alone in predicting and discriminating 60-day outcomes [ 27 ]. Second, the NUTRIC-S score (S as a reference to SAPS III) was recently proposed.…”
Section: Discussionmentioning
confidence: 99%
“…It became a more practical and easier-to-use tool based on the variables that are easily obtained in the critical care setting. Although several studies have validated its diagnostic value as a predictor of malnutrition [ 9 ], the results of these studies were mostly limited to patients receiving only medical treatment [ 10 , 11 , 12 , 13 , 14 ]. In contrast, relatively little information is available for patients who underwent abdominal surgery, despite their having a high risk of malnutrition, which affects the postoperative prognosis.…”
Section: Introductionmentioning
confidence: 99%